1998
DOI: 10.1590/s1415-47571998000300009
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the Pantaneiro horse of the Pantanal region of Brazil

Abstract: Genetic variation at seven red blood cell alloantigen, blood group loci and 10 biochemical genetic loci was examined in 102 Pantaneiro horses from the Pantanal region of Brazil and compared to that of other domestic horse breeds. Measures of both individual genic variation and populational genetic diversity within the Pantaneiro were near the average for domestic horse breeds. From the standpoint of genetic conservation there is no immediate concern for loss of variation within the Pantaneiro. Analysis of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Close inspection of Pantaneiro group showed a clear subdivision of population, and 16 animals split in (Bjørnstad et al, 2000;Cañon et al, 2000;Vilà et al, 2000). The differences obtained from microsatellite analyses are in agreement with the results of Cothran et al (1998), which characterized red blood cell alloantigen, blood group loci and biochemical genetic loci of four Pantaneiro horse populations. The origin of Pantaneiro horse and Uruguay Creole goes back to the colonization, but although they have geographically closely located, there was a clear genetic differentiation between them, as indicated by microsatellites analyses.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Close inspection of Pantaneiro group showed a clear subdivision of population, and 16 animals split in (Bjørnstad et al, 2000;Cañon et al, 2000;Vilà et al, 2000). The differences obtained from microsatellite analyses are in agreement with the results of Cothran et al (1998), which characterized red blood cell alloantigen, blood group loci and biochemical genetic loci of four Pantaneiro horse populations. The origin of Pantaneiro horse and Uruguay Creole goes back to the colonization, but although they have geographically closely located, there was a clear genetic differentiation between them, as indicated by microsatellites analyses.…”
Section: Resultssupporting
confidence: 85%
“…Pantaneiro horse population, compared with other breeds, has a genetic structure; the number of alleles and heterozygosity value demonstrated a high degree of genetic diversity within the breeding nucleus. Cothran et al (1998) observed an excess of heterozygosity in four Pantaneiro populations, and a single statistically significant deviation from HardyWeinberg expectations. They concluded that levels of genetic variability within Pantaneiro breed were at about the normal level for horses.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Cothran et al 17 showed the close genetic relationships of this breed with those from the Iberian Peninsula (Andaluz and Lusitanian) as well as other Brazilian horses, especially Mangalarga. The overall body shape is referred to as conformation.…”
Section: Resultsmentioning
confidence: 80%